The Effect of Education Given to Pregnant Women on Constipation-related Quality of Life and Severity of Constipation - Yüksekol, Özlem Doğan; Baltacı, Nazlı (My University, 2022)
Aim: The purpose of this study was to investigate the effects of education provided to pregnant women with complaints of constipation on their constipation-related quality of life and constipation severity.Methods: This randomized controlled experimental study consisted of an intervention group (n:32) and a control group (n:32). The data were collected by using a Personal Information Form, the Constipation Severity Instrument and the Patient Assessment of Constipation Quality of Life Questionnaire. In data analysis, frequency and percentage calculations, chi-squared, Student’s t-test or Mann-Whitney U test and Person’s correlation analysis were used.Results: After the education, the pregnant women in the intervention group had a lower mean total PAC-QOL score (49.42±4.19) and a lower mean total CSI score (19.40±2.62) than those in the control group (respectively, 74.00±5.47; 39.45±3.21) (p<0.001). Accordingly, the pregnant women who received constipation education had fewer constipation symptoms and higher levels of constipation-related quality of life. It was determined among all participants that, as the severity of constipation symptoms decreased, their quality of life increased (p<0.01).Conclusions: As a result of the education provided to the pregnant women experiencing complaints of constipation, the pregnant women’s constipation-related complaints significantly decreased, and their constipation-related quality of life increased. Nurses are recommended to provide pregnant women experiencing constipation with constipation-related evidence-based care and education.
Keywords: Education; Pregnancy; Constipation; Constipation-related quality of life; Constipation severity